Evolution of community health workers: the fourth stage - Nachiket Mor; Bindu Ananth; Viraj Ambalam; Aquinas Edassery; Ajay Meher; Pearl Tiwari; Vinayak Sonawane; Anagha Mahajani; Krisha Mathur; Amishi Parekh; Raghu Dharmaraju (Frontiers in Public Health, 2023)
This paper examines the comprehensive provider stage (stage 4) with the help of programs that have attempted to explore this stage, using Qualitative Comparative Analysis (QCA) developed by Ragin.
Keywords: Crowd sourcing; Household waste segregation; slogan contest; Environmental health; Community participation